The Concentration of Synaptically Released Glutamate Outside of the Climbing Fiber–Purkinje Cell Synaptic Cleft - Dzubay, Jeffrey A. (J Neurosci, 1999)
AMPA receptors and glutamate transporters expressed by cerebellar Bergmann glial cells are activated by neurotransmitter released from climbing fibers (Bergles et al., 1997). Based on anatomical evidence, this is most likely the result of glutamate diffusing out of the climbing fiber–Purkinje cell synaptic clefts (Palay and Chan-Palay, 1974). We used the change in the EC(50) of the Bergmann glia AMPA receptors produced by cyclothiazide (CTZ) to estimate the concentration of glutamate reached at the glial membrane. The decrease of the EC(50) gives rise to a concentration-dependent potentiation of the AMPA receptor-mediated responses (Patneau et al., 1993). By comparing the increase in amplitude of the AMPA receptor response in the Bergmann glia (840 ± 240%; n= 8) with the shift in the glutamate dose–response curve measured in excised patches (EC(50), 1810 μm in control vs 304 μm in CTZ), we estimate that the extrasynaptic transmitter concentration reaches 160–190 μm. This contrasts with the concentration in the synaptic cleft, thought to rapidly rise above 1 mm, but is still high enough to activate glutamate receptors. These results indicate that the sphere of influence of synaptically released glutamate can extend beyond the synaptic cleft.